Characterizing primary care in breast cancer survivors after completion of cancer therapy - Kendall Kay; Yancen Pan; Jessica Li; Lan Zhang; Vanessa N Torres; Yelba Castellon-Lopez; Meng-Han Tsai; Geetanjali D Datta; Jennifer Henry; Cody Ramin (Cancer Causes & Control, 2026)
Purpose Despite the potential for primary care to optimize comorbidity management among breast cancer survivors, engagement with primary care providers (PCPs) remains low. This study comprehensively examined PCP-led care after breast cancer treatment to identify survivors who may benefit from targeted interventions to improve primary care engagement. Methods We identified 1,582 posttreatment breast cancer survivors from the U.S. Behavioral Risk Factor Surveillance System survey. Weighted multivariable-adjusted logistic regression models were used to examine associations of sociodemographic, lifestyle, clinical, and survivorship-related factors with PCP-led care after cancer treatment. Results Overall, 72% of survivors reported receiving PCP-led follow-up (64% among those aged Conclusion Gaps in PCP-led care after breast cancer treatment underscore the importance of improving access and support for PCP-led engagement throughout survivorship. Future studies are needed to examine barriers to PCP-led care among younger survivors, NH-Black and NH-Asian survivors, and those with heart disease, and to characterize region-specific differences in PCP-led care across the U.S.